Syura ke Pemilu: Evolusi Konsep Kepemimpinan dalam Islam - Maulida Hasanah; Akhmad Zaki Yamani (PT. Pustaka Andil Lestari, 2025)
This study examines general elections (pemilu) as a modern political mechanism that can serve as a contemporary alternative to the khilafah system in Islamic political tradition. Using theological and historical-political approaches, this study explores the fundamental differences between the centralist khilafah system, which is based on religious legitimacy, and the electoral system rooted in popular participation and sovereignty of law. The analysis focuses on the concepts of imamah, syura, and bai’ah in classical Islamic political thought and how these principles have transformed in the context of modern democracy. The study also reviews the responses of various groups, both proponents and opponents of electoral systems, and the normative arguments used to legitimize or reject it. The findings suggest that while khilafah is seen as an ideal system in classical literature, elections can be understood as a relevant instrument within maqashid shariah, ensuring justice, participation, and representation for the ummah. Thus, elections are not simply a Western product but can be contextualized within the framework of Islamic politics as a form of contemporary ijtihad.